“Incorporación de las Infecciones de transmisión sexual, como agravante modificatoria en el delito de violación para proteger la salud de las víctimas”. - Pardo Vega, Jeniffer Nicole (2025)
This curricular integration project, titled: “Incorporating Sexually Transmitted Infections as a Modifying Aggravating Factor in the Crime of Sexual Assault to Protect Victims' Right to Health”, proposes including sexually transmitted infections (STIs) as an aggravating factor in sexual assault cases to ensure proportional penalties and safeguard victims' right to health. STIs such as chlamydia, herpes, and syphilis are frequently found in sexual assault victims and have a high likelihood of reinfection, exacerbating the physical and psychological impact of these crimes. While some STIs are treatable, they are not always detected in time. Ecuadorian law (Article 48, numeral 3 of the COIP) only considers severe, incurable, or fatal diseases as aggravating factors, leaving many cases inadequately addressed. The study highlights deficiencies in the normative and protective systems, noting that victims’ integral reparation is often limited to monetary compensation without ensuring ongoing medical, psychological, and legal follow-up. Furthermore, it underscores the absence of treatment and rehabilitation programs for offenders, hindering efforts to prevent recidivism. Qualitative methods, including interviews and surveys with legal and medical experts, were employed to support this research. Findings reveal a lack of specific regulation in Ecuadorian legislation addressing STI transmission in sexual assault victims and insufficient action by authorities in guaranteeing comprehensive reparation and rehabilitation. The study concludes with proposals to strengthen access to medical, psychological, and legal care for victims and to implement rehabilitation programs for offenders as part of a more holistic approach.